THE EFFECT OF BEHAVIOR-BASED SAFETY IMPLEMENTATION ON UNSAFE ACTIONS AMONG PT X - Asyifa Amalia Samsuri; Farhana Syahrotun Nisa Suratna; Haris Setyawan (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Occupational accidents can result in financial losses for the company and decreased worker productivity. These incidents are often caused by unsafe actions and conditions. At PT X, several work activities pose a high hazard, including being struck by heavy loads, falls from heights, entrapment by machinery, vehicle-related accidents, and fires. Purpose: This study aims to analyze the effect of Behavior-Based Safety implementation on unsafe actions in workers at PT X. Method: This quasi-experimental study using a pre-test and post-test approach with a control group design. In this research, a total of 70 workers will be divided into two groups, namely the intervention group with the application of BBS and the control group. The implementation of BBS consisted of four stages: (1) Define, (2) Observe, (3) Intervention Program, and (4) Test. The study data were processed and analyzed using the SPSS application. Result: The study demonstrated that the implementation of Behavior-Based Safety (BBS) successfully reduced unsafe actions, as reflected in the Mann-whitney Test results showing a ρ-value = 0.043 (ρ-value < 0.05). Conclusion: The application of BBS serve as an effective effort to reduce unsafe worker actions and therebyminimize occupational accidents.